2022
DOI: 10.3389/fcell.2022.857066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of Dental Pulp Stem Cells in Pulp Regeneration: Current Endodontic Progress and Future Perspectives

Abstract: Dental caries is a common disease that not only destroys the rigid structure of the teeth but also causes pulp necrosis in severe cases. Once pulp necrosis has occurred, the most common treatment is to remove the damaged pulp tissue, leading to a loss of tooth vitality and increased tooth fragility. Dental pulp stem cells (DPSCs) isolated from pulp tissue exhibit mesenchymal stem cell-like characteristics and are considered ideal candidates for regenerating damaged dental pulp tissue owing to their multipotenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 186 publications
(231 reference statements)
0
15
0
Order By: Relevance
“…DPSCs with self-renewing, proliferation, and differentiation properties can be a favorable substitute for tissue repair [ 8 , 9 , 11 ]. They have been used in regenerative medicine [ 32 ], including pulp regeneration [ 33 ], oral maxillofacial tissue engineering [ 34 ], and many other diseases [ 35 ], but there are still limitations in their clinical application. Therefore, an effective method to be non-invasive and to accurately track the survival and migration of these grafted cells can open a door in cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPSCs with self-renewing, proliferation, and differentiation properties can be a favorable substitute for tissue repair [ 8 , 9 , 11 ]. They have been used in regenerative medicine [ 32 ], including pulp regeneration [ 33 ], oral maxillofacial tissue engineering [ 34 ], and many other diseases [ 35 ], but there are still limitations in their clinical application. Therefore, an effective method to be non-invasive and to accurately track the survival and migration of these grafted cells can open a door in cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of iron oxide nanoparticles in labeled cells by MRI can be due to the presence of inert magnetite (Fe 3 O 4 ) or maghemite (γ-Fe 2 O 3 ) iron core [ 33 ]. Fe 3 O 4 or γ-Fe 2 O 3 iron cores were also shown to have little or no negative effect on cell proliferation and viability which can explain our results on the absence of any toxicity on cell proliferation, viability, and differentiation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that inflammation at limited levels serves a great promise to sustain dental pulp vitality and regenerate the dental-pulp complex. However, controlling the range of inflammation in the clinical setting is quite challenging [ 19 , 20 ]. Some bioscaffolds, such as CGF, may optimize the balance between the inflammatory and regenerative responses in the infected pulp [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms begin when the carious lesions grow and progress to the dentin ( Selwitz, 2007 ). At this stage, an inflammatory response occurs in the dental pulp, along with pulp tissue ischemia with severe pain ( Kwack and Lee, 2022 ).…”
Section: Introductionmentioning
confidence: 99%